Ready to write 2 : perfecting paragraphs - Blanchard, Karen Lourie; Root, Christine Baker (White Plains, NY : Pearson Education, 2010)
Getting Organized: The key to good writing -- Understanding paragraphs -- Organizing information by time order -- Organizing information by order of importance -- Organizing information by spatial order -- Understanding the writing process -- Supporting the main idea -- Explaining a process -- Writing descriptions -- Expressing your opinion -- Comparing and contrasting -- Analyzing causes and effects -- Writing personal letters and business letters -- Writing.
Previously published as: Ready to Write, A First Composition Text, 3rd ed., 2002.
Keywords: English language; Report writing